Unemployment, public-sector healthcare expenditure and colorectal cancer mortality in the European Union: 1990-2009. - Maruthappu, M; Watson, R; Watkins, J; Williams, C; Zeltner, T; Faiz, O; Ali, R; Atun, R (Springer International Publishing, 2015)
We examined the association between unemployment and government spending on healthcare with colorectal cancer mortality.Retrospective observational study using data from the World Bank and WHO. Multivariate regression analysis was used, controlling for country-specific differences in infrastructure and demographics.A 1 % increase in unemployment was associated with a significant increase in colorectal cancer mortality in both men and women [men: coefficient (R) = 0.0995, 95 % confidence interval (CI) 0.0132-0.1858, P = 0.024; women: R = 0.0742, 95 % CI 0.0160-0.1324, P = 0.013]. A 1 % increase in government spending on healthcare was associated with a statistically significant decrease in colorectal cancer mortality across both sexes (men: R = -0.4307, 95 % CI -0.6057 to -0.2557, P < 0.001; women: R = -0.2162, 95 % CI -0.3407 to -0.0917, P = 0.001). The largest changes in mortality occurred 3-4 years following changes in either economic variable.Unemployment rises are associated with a significant increase in colorectal cancer mortality, whilst government healthcare spending rises are associated with falling mortality. This is likely due, in part, to reduced access to healthcare services and has major implications for clinicians and policy makers alike.